Numerical and analytical solutions for Falkner-Skan flow of MHD Oldroyd-B fluid. Issue 2 (25th February 2014) - Abbasbandy, S.; Hayat, T.; Alsaedi, A.; Rashidi, M.M.
Abstract : Purpose: – In this paper, analysis is presented to investigate the Falkner-Skan flow of magnetohydrodynamic (MHD) Oldroyd-B fluid. The paper aims to discuss these issues. Design/methodology/approach: – In this paper, the authors used two methods: homotopy analysis method and numerical Keller-box method. Findings: – It is observed that skin friction coefficient in Oldroyd-B fluid is larger when compared with viscous fluid. Further, the relaxation and retardation times have opposite effects on the velocity components. Practical implications: – A comparative study between the series and numerical solutions for the skin friction is shown in the paper. The results indicated that both solutions are in well agreement. Originality/value: – This model is investigated for the first time, as the authors know.